A national cross-sectional survey investigating the use of endoscopic ultrasound in the diagnosis and treatment of oesophageal cancer in the UK. Issue 6 (June 2021) - Jones, C.M.; Lyles, A.; Foley, K.G.
Abstract : AIM: To evaluate variation in the pre-pandemic use of endoscopic ultrasound (EUS) for oesophageal cancer diagnosis and treatment planning up to 2019, and which factors contributed to this. MATERIALS AND METHODS: A UK-wide online survey of oesophagogastric multidisciplinary team lead clinicians was undertaken to determine perceptions towards, and the use of, EUS to aid staging and treatment planning in oesophageal cancer. RESULTS: Thirty-five responses were received, representing 97 UK National Health Service Trusts/Health Boards. A majority of centres ( n= 21, 60%) did not have formal written guidance for EUS use. Although all respondents had access to EUS, a perceived lack of utility ( n= 7) and concerns about delaying treatment start dates ( n= 8) each restricted EUS use for a fifth of respondents. For most centres ( n= 24, 68.6%), EUS use is case-specific, whereas for 10 (28.6%) EUS is used for all patients with potentially curable disease. A majority of centres use diagnostic positron-emission tomography for radiotherapy target volume delineation (TVD), whereas 22 (62.9%) use EUS. The factors contributing to decisions to use EUS for staging, TVD and surgical planning varied between centres. The proportion of centre respondents who would request EUS in each of six clinical scenarios varied considerably. CONCLUSION: There were substantial differences in the patient and disease characteristics that are perceived to be indications for EUS use for both staging and treatment planning. Research to clarify in which patients with oesophageal cancer EUS affords benefit is required, as is urgent standardisation of its role in the diagnostic pathway. Highlights: Endoscopic ultrasound (EUS) use varies significantly across the UK. Most centres decide on EUS use on a case-specific basis. Only two thirds of centres use EUS for radiotherapy planning. Patient and disease characteristics used to decide on EUS use vary substantially.